The origins of Greek temple architecture - Pierattini, Alessandro. (Cambridge)
xix, 330 sayfa
Keywords: “In this book, Alessandro Pierattini offers a comprehensive study of the evolution of pre-Archaic Greek temple architecture from the eleventh to the mid-seventh century BC. Demystifying the formative stages of Greek architecture, he traces how temples were transformed from unassuming shrines made of perishable materials into large stone and terracotta monuments. Grounded in archaeological evidence, the volume analyzes the design, function, construction, and aesthetic of the Greek temple. While the book's primary focus is architectural, it also draws on nonarchitectural material culture, ancient cult practice, and social history, which also defined the context that fostered the Greek temple's initial development. In reconstituting this early history, Pierattini also draws attention to new developments as well as legacies from previous eras. Ultimately, he reveals why the temple's pre-Archaic development is not only of interest in itself but also a key to the origins of the Greek monumental architecture of the Archaic period.” --